The Black Border and Fugitive Narration in Black American Literature - Gleich, Paula von (American Frictions, 2022)
This book tests the limits of fugitivity as a concept in recent Black feminist and Afro-pessimist thought. It follows the conceptual travels of confinement and flight through three major Black writing traditions in North America from the 1840s to the early 21st century. Cultural analysis is the basic methodological approach and recent concepts of captivity and fugitivity in Afro-pessimist and Black feminist theory form the theoretical framework.